Preliminary study of Solubilization of phosphates by bacteria - Ramos, A.; Callao, V. (Ars Pharmaceutica (Internet), 1965)
A study of 6 different strains dissolving phosphate is made under two principal aspects: the qualitative action over some mineral phosphates, and the quantitative action over dicalcium phosphate, in the liquid medium.